2015
DOI: 10.1208/s12249-015-0383-0
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-Based Topical Hydrogels of Tenoxicam for Treatment of Arthritis

Abstract: Abstract. Tenoxicam (TNX) is a non-steroidal anti-inflammatory drug (NSAID) used for the treatment of rheumatoid arthritis, osteoarthritis, ankylosing spondylitis, backache and pain. However, prolonged oral use of this drug is associated with gastrointestinal adverse events like peptic ulceration, thus necessitating its development as topical formulation that could obviate the adverse effects and improve patient compliance. The present study was aimed at development of microemulsion-based formulations of TNX f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The resulting material thus gels only in a limited T range centred around human body values, making it possibly promising for pre-clinical and clinical use to facilitate medical treatments and therapies. In addition, we envision applications of such gels in vaccines43 as antigen interacting adjuvant, in inflammation/arthritis44 or bone tissue restoration45 as support for cell migration and adhesion. Our results become particularly interesting for these applications in view of the fact that DNA interacts with RNA and/or proteins at specific oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting material thus gels only in a limited T range centred around human body values, making it possibly promising for pre-clinical and clinical use to facilitate medical treatments and therapies. In addition, we envision applications of such gels in vaccines43 as antigen interacting adjuvant, in inflammation/arthritis44 or bone tissue restoration45 as support for cell migration and adhesion. Our results become particularly interesting for these applications in view of the fact that DNA interacts with RNA and/or proteins at specific oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…One formulation was selected from each category. Viscosity of the vehicle is one of the factors that is speculated to affect the diffusion of the active ingredient and the release rate from the dosage form [ 18 , 19 ]. In this study we manipulated the lipid content and the lipid composition to create a wide range of viscosity among the compounded dosage forms.…”
Section: Resultsmentioning
confidence: 99%
“…2 In addition to the above characteristics, the soft and rubbery nature of hydrogels minimises irritation to surrounding tissue. Their highly porous structure which can easily be tuned by controlling the density of cross-links in the gel matrix and the affinity of the hydrogels for the aqueous environment in which they are swollen 3 is also an advantage. The porosity of hydrogels also permits loading of drugs into the gel matrix and subsequent drug release at a rate, which is dependent on the diffusion coefficient of the small molecule or macromolecule through the gel network.…”
Section: Introductionmentioning
confidence: 99%
“…The porosity of hydrogels also permits loading of drugs into the gel matrix and subsequent drug release at a rate, which is dependent on the diffusion coefficient of the small molecule or macromolecule through the gel network. 3 Tetracarpidium conophorum, commonly called the African walnut plant, whose ethanolic extract would make up the second component of the formulation of study, is a perennial climbing shrub 10 to 20 feet long, found growing wild in forest zones of sub-Sahara Africa, including Nigeria. Studies have shown that the African walnut possess some beneficial properties like antibacterial, 4 antioxidant 4,5 and immune-stimulating activities.…”
Section: Introductionmentioning
confidence: 99%